Inclusive teaching strategies are not widely used by male physics instructors - Md Sanyat Rabby; Charles Henderson (Physical Review Physics Education Research)
Introductory physics is a gateway course that is required for many science, technology, engineering, and mathematics (STEM) majors. In introductory physics courses, women and racially minoritized students often have lower grades and higher attrition than white men. Inclusive teaching is widely recommended to ensure that all students have the opportunity to fully participate and succeed in the learning process. Thus, inclusive teaching practices may help increase the diversity of people in STEM majors and careers. However, these recommended inclusive teaching practices are not widely used in introductory physics courses. This study seeks to better understand the extent to which introductory college-level physics instructors use inclusive teaching strategies as well as their reasons for the use or nonuse of such practices. We conducted semi-structured interviews with 11 male instructors from a variety of higher education institutions in Michigan who taught introductory calculus-based physics courses in Spring 2022. The participants were asked to describe their use of and beliefs about 23 specific inclusive teaching strategies. Results show that few of these instructors are aware of the full range of inclusive teaching strategies. Most instructors are aware of inclusive teaching strategies that are related to active learning and frequently articulate valid reasons for implementing these strategies. However, when implementing inclusive teaching strategies, they often do not do so in ways that are known to be most effective. Instructors are less aware of and less willing to use inclusive teaching practices that require acknowledging differences in students’ identities. Their reasoning is that physics is an objective science that has nothing to do with race, gender, or other aspects of identity. Overall, this preliminary study suggests that significant work is needed to help introductory physics instructors understand, value, and implement the full range of inclusive teaching strategies.